High-temperature-oxidation-resistant SiC / SiC-CrSi2-ZrB2 composite coating on surface of carbon-based composite material and preparation method
By depositing a pyrolytic carbon layer on the surface of the carbon-based composite material and preparing the SiC/SiC-CrSi2-ZrB2 composite coating, the problem of oxidation of carbon-based composite materials in high-temperature aerobic environment is solved, and the effect of significantly improving the material strength and oxidation protection time is achieved.
Patent Information
- Application Number
- CN202411777025.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
AI Technical Summary
The carbon-based composite material begins to oxidize in an aerobic environment above 400℃, resulting in failure in ultra-high temperature oxygen-containing environments and failing to meet the practical application requirements.
The SiC/SiC-CrSi2-ZrB2 composite coating was used to deposit a pyrolytic carbon layer on the surface of the carbon-based composite material, and the SiC porous layer was prepared by slurry coating and heat treatment, and then the SiC/SiC-CrSi2-ZrB2 coating was obtained by embedding and permeation method.
Effectively prevent carbon-based composites from failing in high-temperature oxidation environments, improve the density and bonding properties of the coating, enhance the bending strength of carbon-based composites, and provide at least 541 hours of oxidation protection at 1773K.
Smart Images

Figure CN119569481A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-oxidation of carbon-based composite materials, and in particular to a high-temperature oxidation-resistant SiC / SiC-CrSi2-ZrB2 coating on the surface of a carbon-based composite material and a preparation method thereof. Background Art
[0002] With the rapid development of ultra-high-speed aircraft, researchers have a considerable demand for ultra-high temperature structural materials for key aircraft components. This demand requires characteristics such as light weight, high temperature resistance, high specific strength, chemical corrosion, and thermal shock resistance. Carbon-based composites refer to all-carbon composites made by densification treatment with carbon fibers as reinforcements and carbon materials as matrices. They have a series of excellent properties such as low density, high specific strength, and thermal shock resistance. In particular, they are considered to be promising candidate materials due to their high strength retention rate in ultra-high temperature oxygen-free environments. However, carbon-based composites begin to oxidize in an oxygen environment above 400°C. In an ultra-high temperature oxygen-containing environment, carbon-based composites without any anti-oxidation measures will quickly fail, so they cannot meet the requirements of practical applications. Preparing anti-oxidation coatings is an effective way to solve this problem. Silicon-based ceramics and ultra-high temperature ceramics (UHTCs) have high melting points, high thermal conductivity, good anti-oxidation and anti-ablation properties, and are good high-temperature anti-oxidation materials.
[0003] Patent "CN115784776B" discloses a method for preparing a MoSi2-ZrB2 composite coating, which effectively solves the silicification damage problem during the embedding process of the C / C matrix and realizes a large-scale uniform distribution of MoSi2-ZrB2 in the coating. However, a large amount of gas (CO, CO2 and MoO3, etc.) is generated during the oxidation process of the coating, which destroys the integrity of the oxide layer, so the protection time of the coating is short.
[0004] Reference 1 "Oxidation and mechanical properties of SiC / SiC-MoSi2-ZrB2 coating for carbon / carbon composites. Xiyuan Yao, Hejun Li, Yulei Zhang, Yongjie Wang. Journal of Materials Science & Technology, 2014, 30 (2): 123-127." A SiC / SiC-MoSi2-ZrB2 coating was prepared on the surface of a C / C composite material using a two-step embedding method. After oxidation at 1773K for 510h, the weight loss rate of the coating system was only 0.5%. However, the preparation temperature of this process is high, which is prone to thermal stress concentration and induces cracking of the coating. In addition, during the embedding infiltration process, molten silicon infiltrates into the C / C matrix, undergoes a silicification reaction to generate SiC hard and brittle phases, and reduces the mechanical properties of the C / C composite material.
[0005] Reference 2 "HfSi2-HfB2-SiC coating prepared at low temperature to protect SiC-coated C / C composites against oxidation at 1473–1973K. Xiaofei Zhu, Chenyang Ou, Tao Li, Yulei Zhang, Junshuai Lv, Ruicong Chen. Ceramics International, 2024, 50(8): 13490-13499." HfSi2-HfB2-SiC coating was prepared on the surface of SiC-coated C / C composite by combining slurry impregnation and oxidative sintering. The coating can provide 500h of oxidation protection for C / C composite at 1773K. However, the coating prepared by this method has poor adhesion to the substrate, is easy to fall off in the alternating temperature field, and the density of the coating is difficult to meet the requirements. Summary of the invention
[0006] In order to solve the deficiencies of the prior art, the present invention proposes a high temperature oxidation resistant SiC / SiC-CrSi2-ZrB2 coating on the surface of a carbon-based composite material and a preparation method thereof. The technical solution of the present invention is as follows:
[0007] A SiC / SiC-CrSi2-ZrB2 composite coating resistant to high temperature oxidation on the surface of a carbon-based composite material. The composite coating comprises a SiC transition layer and a SiC-CrSi2-ZrB2 outer coating. The transition layer covers the carbon-based composite material, and the outer coating covers the transition layer.
[0008] As an improvement, a pyrolytic carbon layer is provided on the surface of the carbon-based composite material, and the SiC transition layer covers the pyrolytic carbon layer.
[0009] The preparation method of the present invention comprises the following steps:
[0010] Step 1: placing the carbon-based composite material in a deposition furnace, and depositing a pyrolytic carbon layer on the surface of the carbon-based composite material;
[0011] Step 2: Weigh Si powder, C powder, phenolic resin, silica sol and anhydrous ethanol and mix them thoroughly and evenly to obtain a mixed slurry;
[0012] Step 3: evenly apply the mixed slurry obtained in step 2 to the carbon-based composite material with a pyrolytic carbon layer on the surface obtained in step 1, dry it, and then heat-treat it under inert atmosphere to obtain a carbon-based composite material coated with a SiC porous layer;
[0013] Step 4: Weigh the Cr, Si, C and ZrB2 powders and mix them thoroughly;
[0014] Step 5: embedding the carbon-based composite material coated with the SiC porous layer obtained in step 3 into the mixed powder obtained in step 4, and placing the mixed powder in a graphite crucible;
[0015] Step 6: heat-treating the graphite crucible obtained in step 5 under the protection of an inert atmosphere to obtain a carbon-based composite material having a high-temperature oxidation-resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface.
[0016] As an improvement, the mass ratio (wt.%) of Si powder, C powder, phenolic resin, silica sol and anhydrous ethanol in step 2 is (30-35):(5-10):(6-10):(3-5%):(40-65).
[0017] As an improvement, in step 3, the heat treatment temperature is 1723-1823 K, the insulation time is 1-3 h, and the heating rate is 3-10 K / min.
[0018] As an improvement, the mass ratio of Cr, Si, C and ZrB2 powder in step 4 is (20-25):(55-65):(10-15):(5-10).
[0019] As an improvement, in step 6, the heat treatment temperature is 2173-2373 K, the insulation time is 1-3 h, and the heating rate is 5-10 K / min.
[0020] The advantages of the present invention are:
[0021] First, a layer of pyrolytic carbon is deposited on the surface of the carbon-based composite material. The homogeneous and dense pyrolytic carbon layer blocks and consumes free silicon, effectively solving the problem of silicification damage of the carbon-based composite material, and is conducive to the formation of a SiC coating with a dense structure and uniform composition. Secondly, a SiC porous layer with nanowires is prepared by slurry brushing combined with heat treatment. The porous structure can improve the distribution uniformity of the CrSi2-ZrB2 ceramic phase. The SiC nanowires have a toughening effect on the final prepared coating, thereby reducing the number of defects such as cracks in the coating. Finally, Si, C, Cr, and ZrB2 are used as raw materials, and the SiC / SiC-CrSi2-ZrB2 coating is obtained on the above basis by the embedding infiltration method. During the embedding process, the molten silicon fully fills the pores in the porous layer, and also effectively fuses the inner and outer layers together, improving the density and bonding performance of the inner and outer coatings. The SiC / SiC-MoSi2-ZrB2 composite coating also plays a bearing role, so the bending strength of the coated carbon-based composite material is increased by 24.6%. After the coated carbon-based composite material was oxidized in air at 1773K for 541h, the mass loss of the coated sample was only 1.48%. The Cr2O3 formed after the oxidation of CrSi2 partially dissolved in the B2O3 glass, increasing the viscosity of B2O3. In addition, Cr and Zr atoms can co-exist stably in the SiO2 lattice structure in the form of co-doping, which improves the bonding force between the SiO2 lattice interfaces. In addition, the high-melting-point ZrO2 and Cr2O3 act as "pinning phases" to inhibit the generation and expansion of microcracks. The composite glass layer formed after oxidation has high high-temperature stability, low oxygen diffusion rate and self-healing ability, which can provide long-term oxidation protection for carbon-based composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a process flow chart of the present invention.
[0023] Figure 2 This is a comparison chart of the flexural strength of the SiC / SiC-CrSi2-ZrB2 coated carbon-based composite material prepared in Example 1 of the present invention (right) and the original composite material without coating added in the control example (left).
[0024] Figure 3 This is the bending fracture morphology of SiC / SiC-CrSi2-ZrB2 coated C / C composite material.
[0025] Figure 4 The oxidation mass change curves of the SiC / SiC-CrSi2-ZrB2 coated carbon-based composite material prepared in Example 1 of the present invention at different temperatures: (a) 1773K, (b) 1973K.
[0026] Figure 5This is a SEM image of the SiC / SiC-CrSi2-ZrB2 coated carbon-based composite material prepared in Example 1 of the present invention after oxidation at 1773K for 541h. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0028] Example 1
[0029] A high temperature oxidation resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface of a carbon-based composite material and a preparation method thereof, comprising the following steps:
[0030] Step 1: Remove burrs and edges from the carbon-based composite material, clean it, place it in a deposition furnace, cool it to room temperature, and take a sample to obtain a carbon-based composite material with a surface layer covered with PyC;
[0031] Step 2: Weigh 30wt.% Si powder, 10wt.% C powder, 6wt.% phenolic resin, 4wt.% silica sol and 50wt.% anhydrous ethanol and mix them thoroughly and evenly;
[0032] Step 3: The mixed slurry obtained in step 2 is evenly applied to the carbon-based composite material with a pyrolytic carbon layer on the surface obtained in step 1, and after drying, it is placed in a high-temperature heat treatment furnace, and the temperature is raised to 1473K at 10K / min under the protection of inert gas, and then the temperature is raised to 1773K at 5K / min, and the temperature is kept for 2h. After cooling to room temperature with the furnace, a carbon-based composite material coated with a SiC porous layer is obtained;
[0033] Step 4: Weigh 25wt.% Cr, 10wt.% C, 55wt.% Si and 10wt.% ZrB2 and mix them uniformly;
[0034] Step 5: The carbon-based composite material coated with the SiC porous layer obtained in step 3 is buried in a graphite crucible containing the mixed powder obtained in step 4, and placed in a high-temperature heat treatment furnace, and the temperature is raised to 2273K at 10K / min, and the temperature is kept for 1.5 hours. After cooling to room temperature in the furnace, a carbon-based composite material with a high-temperature oxidation-resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface is obtained.
[0035] In contrast, this embodiment sets an original carbon-based composite material without adding a coating as a control example for comparative testing.
[0036] from Figure 2It can be seen that compared with the original carbon-based composite material, the bending strength of the SiC / SiC-CrSi2-ZrB2 coated carbon-based composite material is increased by 24.6%.
[0037] from Figure 3 It can be seen that no obvious silicification-enriched area is observed inside the C / C matrix ( Figure 4 a), but there are a lot of long pulled-out carbon fibers. It can also be seen from the enlarged picture ( Figure 4 b), there is no rough morphology formed by the accumulation of silicified particles in the fracture. Therefore, the PyC layer encapsulating the C / C matrix effectively delays the penetration of free silicon into the matrix during the embedding process.
[0038] from Figure 4 It can be seen that the mass loss of the prepared SiC / SiC-CrSi2-ZrB2 coated carbon-based composite material sample after oxidation at 1773K for 541h is only 1.48%, and the mass loss of the sample after oxidation at 1973K for 10h is only 4.01%.
[0039] from Figure 5 It can be seen that after the prepared SiC / SiC-CrSi2-ZrB2 coated carbon-based composite material was oxidized at 1773K for 541h, the coating surface was covered with a complete oxide layer. Therefore, the SiC / SiC-CrSi2-ZrB2 coating can provide at least 541h of oxidation protection for the carbon-based composite material at 1773K.
[0040] Example 2
[0041] A high temperature oxidation resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface of a carbon-based composite material and a preparation method thereof, comprising the following steps:
[0042] Step 1: Remove burrs and edges from the carbon-based composite material, clean it, place it in a deposition furnace, cool it to room temperature, and take a sample to obtain a carbon-based composite material with a surface layer covered with PyC;
[0043] Step 2: Weigh 35wt.% Si powder, 5wt.% C powder, 6wt.% phenolic resin, 4wt.% silica sol and 50wt.% anhydrous ethanol and mix them thoroughly and evenly;
[0044] Step 3: The mixed slurry obtained in step 2 is evenly applied to the carbon-based composite material with a pyrolytic carbon layer on the surface obtained in step 1, and after drying, it is placed in a high-temperature heat treatment furnace, and the temperature is increased to 1473K at 3K / min under the protection of inert gas, and then the temperature is increased to 1723K at 5K / min, and the temperature is kept for 3 hours. After cooling to room temperature with the furnace, a carbon-based composite material coated with a SiC porous layer is obtained;
[0045] Step 4: Weigh 20wt.% Cr, 15wt.% C, 60wt.% Si and 5wt.% ZrB2 and mix them uniformly;
[0046] Step 5: The carbon-based composite material coated with the SiC porous layer obtained in step 3 is buried in a graphite crucible containing the mixed powder obtained in step 4, and placed in a high-temperature heat treatment furnace, and the temperature is raised to 2173K at 10K / min and kept at this temperature for 1 hour. After cooling to room temperature in the furnace, a carbon-based composite material with a high-temperature oxidation-resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface is obtained.
[0047] Example 3
[0048] A high temperature oxidation resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface of a carbon-based composite material and a preparation method thereof, comprising the following steps:
[0049] Step 1: Remove burrs and edges from the carbon-based composite material, clean it, place it in a deposition furnace, cool it to room temperature, and take a sample to obtain a carbon-based composite material with a surface layer covered with PyC;
[0050] Step 2: Weigh 35wt.% Si powder, 5wt.% C powder, 10wt.% phenolic resin, 5wt.% silica sol and 45wt.% anhydrous ethanol and mix them thoroughly and evenly;
[0051] Step 3: The mixed slurry obtained in step 2 is evenly applied to the carbon-based composite material with a pyrolytic carbon layer on the surface obtained in step 1, and after drying, it is placed in a high-temperature heat treatment furnace, and the temperature is raised to 1473K at 3K / min under the protection of inert gas, and then the temperature is raised to 1823K at 10K / min, and the temperature is kept for 1h, and the carbon-based composite material coated with a SiC porous layer is obtained after cooling to room temperature with the furnace;
[0052] Step 4: Weigh 25wt.% Cr, 10wt.% C, 55wt.% Si and 10wt.% ZrB2 and mix them uniformly;
[0053] Step 5: The carbon-based composite material coated with the SiC porous layer obtained in step 3 is buried in a graphite crucible containing the mixed powder obtained in step 4, and placed in a high-temperature heat treatment furnace, and the temperature is raised to 2373K at 5K / min, and the temperature is kept for 3 hours. After cooling to room temperature in the furnace, a carbon-based composite material with a high-temperature oxidation-resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface is obtained.
[0054] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A SiC / SiC-CrSi2-ZrB2 composite coating resistant to high temperature oxidation on the surface of a carbon-based composite material, characterized in that: The composite coating comprises a SiC transition layer and a SiC-CrSi2-ZrB2 outer coating, wherein the transition layer is covered on the carbon-based composite material, and the outer coating is covered on the transition layer.
2. The high temperature oxidation resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface of a carbon-based composite material according to claim 1, characterized in that: A pyrolytic carbon layer is provided on the surface of the carbon-based composite material, and the SiC transition layer covers the pyrolytic carbon layer.
3. A method for preparing a high temperature oxidation resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface of a carbon-based composite material, characterized in that: The steps include: Step 1: placing the carbon-based composite material in a deposition furnace, and depositing a pyrolytic carbon layer on the surface of the carbon-based composite material; Step 2: Weigh Si powder, C powder, phenolic resin, silica sol and anhydrous ethanol and mix them thoroughly and evenly to obtain a mixed slurry; Step 3: evenly apply the mixed slurry obtained in step 2 to the carbon-based composite material with a pyrolytic carbon layer on the surface obtained in step 1, dry it, and then heat-treat it under inert atmosphere to obtain a carbon-based composite material coated with a SiC porous layer; Step 4: Weigh the Cr, Si, C and ZrB2 powders and mix them thoroughly; Step 5: embedding the carbon-based composite material coated with the SiC porous layer obtained in step 3 into the mixed powder obtained in step 4, and placing the mixed powder in a graphite crucible; Step 6: heat-treating the graphite crucible obtained in step 5 under the protection of an inert atmosphere to obtain a carbon-based composite material having a high-temperature oxidation-resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface.
4. The method for preparing a high temperature oxidation resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface of a carbon-based composite material according to claim 3, characterized in that: In step 2, the mass ratio (wt.%) of Si powder, C powder, phenolic resin, silica sol and anhydrous ethanol is (30-35):(5-10):(6-10):(3-5):(40-65).
5. The method for preparing a high temperature oxidation resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface of a carbon-based composite material according to claim 3, characterized in that: In step 3, the heat treatment temperature is 1723-1823 K, the insulation time is 1-3 h, and the heating rate is 3-10 K / min.
6. The method for preparing a surface carbon-based composite material high temperature oxidation resistant SiC / SiC-CrSi2-ZrB2 composite coating according to claim 3, characterized in that: In step 4, the mass ratio of Cr, Si, C and ZrB2 powder is (20-25):(55-65):(10-15):(5-10).
7. The method for preparing a high temperature oxidation resistant SiC / SiC-CrSi2-ZrB2 composite coating on the surface of a carbon-based composite material according to claim 3, characterized in that: In step 6, the heat treatment temperature is 2173-2373 K, the insulation time is 1-3 h, and the heating rate is 5-10 K / min.
Citation Information
Patent Citations
Method for preparing silicon carbide nanowire porous layer on surface of carbon / carbon composite material
CN106673708A
Oxidation-induced shape memory fiber as well as preparation method and application thereof
CN111196733A
MoSi2-ZrB2-rich anti-oxidation coating uniformly distributed on surface of carbon / carbon composite material in large range and preparation method of MoSi2-ZrB2-rich anti-oxidation coating
CN115784776A
Oxidation resistant c / C composite material and its production
JP1999292645A
Ceramic composite and process for production thereof
US5316987A